2022
DOI: 10.1038/s42003-022-03705-1
|View full text |Cite
|
Sign up to set email alerts
|

NUPR1 protects against hyperPARylation-dependent cell death

Abstract: Proteomic, cellular and biochemical analysis of the stress protein NUPR1 reveals that it binds to PARP1 into the nucleus and inhibits PARP1 activity in vitro. Mutations on residues Ala33 or Thr68 of NUPR1 or treatment with its inhibitor ZZW-115 inhibits this effect. PARylation induced by 5-fluorouracil (5-FU) treatment is strongly enhanced by ZZW-115 and associated with a decrease of NAD+/NADH ratio and rescued by the PARP inhibitor olaparib. Cell death induced by ZZW-115 treatment of pancreas cancer-derived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…NUPR1 is a nuclear stress protein which is able to bind to PARP1 and inhibit its enzymatic activity. Pharmacological inhibition of NUPR1 causes deleterious PARylation, mitochondrial dysfunction and cell death (Santofimia-Castano et al, 2022). Han et al found that SNORA73, a chromatin-associated small nucleolar RNAs, restrains PARP1 auto-PARylation and contributes to genome instability in hematopoietic malignancy (Han et al, 2022).…”
Section: Negative Regulators Of Parp1 Catalytic Activitymentioning
confidence: 99%
“…NUPR1 is a nuclear stress protein which is able to bind to PARP1 and inhibit its enzymatic activity. Pharmacological inhibition of NUPR1 causes deleterious PARylation, mitochondrial dysfunction and cell death (Santofimia-Castano et al, 2022). Han et al found that SNORA73, a chromatin-associated small nucleolar RNAs, restrains PARP1 auto-PARylation and contributes to genome instability in hematopoietic malignancy (Han et al, 2022).…”
Section: Negative Regulators Of Parp1 Catalytic Activitymentioning
confidence: 99%
“…Parthanatos has also been involved in human psoriasis in which PARP1 is overactivated downstream of the NAD + generating enzyme nicotinamide phosphoribosyltransferase (NAMPT) and the translocation of AIF from mitochondria to nuclei can be observed in skin lesions [ 26 ]. As an aside, cancer cells can die in response to specific drugs or drug combinations in a PARP1-dependent fashion [ 27 29 ]. Altogether, it appears that, outside of the realm of oncology, PARP1 inhibition might be useful for the treatment of diseases, many of which are caused by the acute, massive or chronic, insidious loss of neurons.…”
Section: Pro-death Activity Of Parp1 In Parthanatosmentioning
confidence: 99%